2009
DOI: 10.1002/bit.22584
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a biofilm membrane reactor and its prospects for fine chemical synthesis

Abstract: Biofilms are known to be robust biocatalysts. Conventionally, they have been mainly applied for wastewater treatment, however recent reports about their employment for chemical synthesis are increasingly attracting attention. Engineered Pseudomonas sp. strain VLB120DC biofilm growing in a tubular membrane reactor was utilized for the continuous production of (S)-styrene oxide. A biofilm specific morphotype appeared in the effluent during cultivation, accounting for 60-80% of the total biofilm irrespective of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
82
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 39 publications
0
82
0
Order By: Relevance
“…These results were similar to those of earlier studies conducted in other biofilm reactor formats for styrene oxide synthesis, such as tubular, solid support membrane aerated reactors. These experiments also showed that the styrene oxide formation rate increased concomitantly with the biofilm biomass and was not hampered by either substrate or product (10,11).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…These results were similar to those of earlier studies conducted in other biofilm reactor formats for styrene oxide synthesis, such as tubular, solid support membrane aerated reactors. These experiments also showed that the styrene oxide formation rate increased concomitantly with the biofilm biomass and was not hampered by either substrate or product (10,11).…”
Section: Discussionmentioning
confidence: 60%
“…than their planktonic or freely swimming counterparts (7,9,16,19,29,40). There has been growing interest in recent years in the exploitation of these robust catalysts for biotechnological applications (e.g., biotransformations) to produce value-added chemicals (10,11,12,27). These studies have shown that the use of biofilms may overcome major bottlenecks in classical biocatalysis processes, such as substrate/product toxicity and short-term biocatalytic stability.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose and organic acid concentrations in the aqueous phase were determined by high-performance liquid chromatography (HPLC) as described before (23).…”
Section: Figmentioning
confidence: 99%